Evaluation and management of urethral calculi - Ameen, Ali Abdulqader; Kegham, Hrair Haik; Abid, Ali Hussein (International Surgery Journal, 2017)
Background: To evaluate the presentation, management and outcome of patient with urethral calculi in addition to determine the most common type of calculi encountered in those patients and the chemical composition of those calculi to prevent their recurrence. Methods: Sixty-nine patients with urethral calculi, 63 males and six females were included in this study at Al-Yarmouk teaching hospital, Bagdad, Iraq from April 2016 to April 2017. The diagnosis of urethral calculi was based mainly on the clinical presentation and cystoscopy evaluation in addition to the history, examination and investigations. Results: All together Sixty-nine patients were recruited in this study [63 male (91.3%) and 6 females (8.6%)], regarding sex distributions of patients the largest number of patients with urethral calculi were found in male between 21-40 years old, the most common presenting symptom was dysuria (60.8%), the presentation of pediatric urethral calculi was different (any suspicion of urethral mass on palpation gave high index of suspicion of urethral calculi). Conclusions: Nephrolithiasis especially renal calculi represent a widespread problem, recurrent UTI is one of the leading risk factor in urinary calculi and should be vigorously treated and any case should be in investigated carefully and chemically analysed to prevent further attacks and recurrence in future. Unbalanced diet with poor hygiene especially for the urethral calculi plays an additional role in the pathogenesis of urethra calculi.